Second-Order Derivative UV Spectrophotometric and RP-HPLC Methods for the Analysis of Vildagliptin and Application for Dissolution Study - Thomas Barden, Amanda; Piccoli, Bruna L; Volpato, Nadia Maria; Steppe, Martin (Drug Analytical Research, 2026)
This study describes two analytical methods, by second-order derivative UV spectrophotometric by HPLC, for determination of vildagliptin, a drug used for treatment of type 2 Diabetes Mellitus that belongs to a therapeutic class called inhibitors of dipeptidyl peptidase 4. The methods were validated in accordance with ICH and USP requirements. Analyses by UV derivative method were performed at 220 nm, which was the zero crossing point of excipient solutions. HPLC was optimized and the analysis was carried out using a Zorbax Eclipse Plus RP-C8 column (150 mm × 4.6 mm, 5 μm), detection at 207 nm, and potassium phosphate buffer solution pH 7.0 : acetonitrile (85:15, v/v) as mobile phase. In dissolution test, the conditions used were 0.01 mol L-1 hydrochloric acid in 900 mL of dissolution medium, USP apparatus 2 (paddle) and 50 rpm stirring speed. Both methods were successfully applied for analysis of dissolution samples from marketed vildagliptin tablets.